Regulatory peculiarities of the use of road signs 5.15.1, 5.15.2 and marking 1.18 on road sections with traffic of fixed-route vehicles - G. V. Abakumov; A. V. Pistsov (Архитектура, строительство, транспорт)
The article deals with the problem of violations of traffic rules by bus drivers when passing intersections. Violations of different nature in the presence of road signs 5.15.1 and 5.15.2, as well as the lines of road markings 1.18 are given. There are presented specific locations in the city of Tyumen, where drivers commit intentional and unintentional violations. Court practice on the issues of offenses at intersections by a route vehicle is analyzed. Possible ways of solving this problem, including at the legislative level, are suggested.